Análise filogenética de amostras de vírus da raiva de herbívoros no Rio Grande do Sul (2012-2017) e validação de um teste de RT-PCR em tempo real para diagnóstico - Almeida, Gisane Lanes de (2020)
Rabies virus (Rabies lyssavirus, RABV) is the agent of rabies, a zoonotic disease distributed worldwide, characterized by severe neurological signs of course generally fatal in domestic and wild mammals. The RABV belongs to the order Mononegavirales, family Rhabdoviridae and genus Lyssavirus. The RABV genome consists of a single-stranded, negative-sense RNA molecule of approximately 12 kilobases (kb) containing 5 genes, including the highly conserved nucleoprotein (N) gene. The N gene has been widely used as a target in phylogenetic studies and for development of molecular tests for diagnosis. In a first study, we describe a phylogenetic analysis of 145 RABV recovered from herbivorous from Rio Grande do Sul state (RS) between 2012 and 2017, based on partial sequence analysis of the N gene. These sequences displayed a high sequence nucleotide (nt) identity and amino acid (aa) similarity to each other and with bovine and hematophagous bat RABV sequences. The viruses segregated into two distinct clusters. Cluster 1 comprised RABV sequences covering the whole studied period, whereas cluster 2 grouped a lower number of viruses from 2013, 2014, 2015 and 2017. In some cases, viruses obtained from the same region within a short period of time grouped to distinct clusters or sub-clusters, indicating the co-circulation of distinct virus lineages in these outbreaks. The segregation into sub-clusters was also observed for viral sequences obtained from the same region at different times, indicating the involvement of distinct viruses. The second study reports the development and validation of a real-time reverse transcription quantitative PCR (RT-qPCR) for diagnostics of rabies in cattle. The primers were designed targeting the highly conserved N gene of RABV from samples obtained from cattle in RS, obtained from GenBank. The detection limit corresponded to 12.99 DNA copies and the intra- and inter-run repeatability was adequate. Non-specific amplification with a range of other pathogens causing neurological syndromes similar to rabies in cattle in RS, as well as cross-contamination were not detected. Bovine brain samples from 21 suspected cases of rabies were tested with the new RABV RT-qPCR assay and with a gold-standard fluorescent antibody test (FAT) and the sensitivity and specificity of the RT-qPCR assay were determined. Both the sensitivity and specificity of the RT-qPCR were 100%. In summary, the studies presented in this Thesis revealed a high conservation of N protein gene and the circulation of two lineages and different sublineages of RABV in the RS, confirming the suitability of N gene to study the genetic relationships among RABV isolates. Furthermore, the RABV RT-qPCR assay provides is analytically and diagnostically sensitive and specific. Thus, this assay may be very useful for a rapid, sensitive and specific diagnosis of rabies in cattle.